Effect of Postural Stabilization Exercises in Combination with Cervical Stabilization Exercises on Craniovertebral Angle, Pain, Disability, and Quality of Life in Patients with Chronic Neck Pain: A Randomized Controlled Trial - Mehmetoglu, Golgem; Yuksel, Inci (Mdpi, 2025)
Objective: The aim of the study was to evaluate the effect of postural stabilization exercises, in addition to cervical stabilization (CS), on the craniovertebral angle (CVA), pain, neck disability index (NDI), and quality of life in people with chronic neck pain. Methods: This study was performed on 60 women with chronic neck pain, aged 20-60 years, who were randomly divided into two groups. Individuals in the first group underwent CS exercises, in addition to scapular and lumbopelvic stabilization (SLPS) exercises, three times a week for 6 weeks. The individuals in the second group underwent only CS exercises for the same period. Moreover, stretching exercises and a 20 min hot pack were applied to the muscles around the neck of all patients. The CVA was measured using photogrammetry. The visual analog scale (VAS) was used to assess pain. The disability level was measured using the NDI. The Turkish version of the 36-Item Short-Form Health Survey (SF-36) was used to assess quality of life. The assessments were conducted before treatment, after treatment, and at the 2-month follow-up. To assess changes over time and between groups, a two-way repeated measures analysis of variance (ANOVA) was conducted. Results: Post-treatment measurements revealed significant differences favoring the SLPS group. The VAS and NDI scores were markedly lower in the SLPS group than in the CS group, both post-treatment (p < 0.001) and at follow-up (p < 0.001). The CVA was significantly greater in the SLPS group at both the post-treatment (p < 0.001) and follow-up (p < 0.001) assessments. However, in all sub-parameters except the SF-36 general health subscale, the SLPS group reported higher scores than the CS group post-treatment and at follow-up. Effect sizes for between-group comparisons ranged from moderate to very large (Cohen's d = 0.65 to 2.31), and partial eta-squared (eta(2)) values indicated moderate to large effect magnitudes (eta(2) = 0.09 to 0.48), supporting the clinical relevance of the findings. Conclusion: In individuals with neck pain, including SLPS exercises in the treatment program, rather than just exercises for the cervical region, provides more positive results in terms of reducing disability and pain and increasing functionality. Clinical Trial Registration Number: NCT06578481.
Keywords: chronic neck pain; craniovertebral angle; lumbopelvic muscle exercises; scapular stabilization; postural stabilization